DEVELOPMENT OF A TORQUE METER FOR FISHING VESSELS - PILLAI, S AYYAPPAN; TAMPI, S T (Fishery Technology, 2017)
The paper describes the development of an electronic instrument to measure the torque developed on the propeller shaft of fishing vessels at various speeds of the propeller. By measuring the torque, it is possible to determine the actual power transmitted from the engine gear-box unit to the propeller so that propeller efficiency can be evaluated and the optimum size of the propeller for a specific engine and vessel can be determined.